Gynecological radio-induced secondary malignancy after a gynecological primary tumor: a rare entity and a challenge for oncologists. Issue 10 (3rd October 2022) - Barcellini, Amelia; Dominoni, Mattia; Gardella, Barbara; Mangili, Giorgia; Orlandi, Ester
Abstract : The management of radiation-induced secondary malignancies in the female genital tract after pelvic radiation treatment for a primary gynecological tumor is a challenge for multidisciplinary teams that follow survivors. Considering the lack of data on the incidence of this disease and the absence of guidelines for its management, in this review, the available literature is analyzed to determine the characteristics and the clinical management of gynecological radiation-induced secondary malignancies. Gynecological radiation-induced secondary malignancies were found to be predominantly more aggressive, poorly differentiated, and had rare histologic types compared with sporadic tumors. The management is influenced by previous radiation doses and the localization of the radiation-induced secondary malignancies. Surgery, when feasible, was the cornerstone; re-irradiation was an option when a surgical approach was not feasible and high-dose conformal techniques should be preferred considering the need to spare previously irradiated surrounding normal tissues. Clinical outcomes, when reported, were poor in terms of local control and survival. Given the difficulty in managing these uncommon malignancies, a centralization of care in sites that are connected to research networks actively partaking in international discussions and with higher expertise in complicated surgery or radiotherapy should be considered to improve clinical outcomes.